An endometrial receptivity scoring system evaluated by ultrasonography in patients undergoing frozen–thawed embryo transfer: a prospective cohort study - Ouyang, Yan; Peng, Yangqin; Mao, Yuyao; Zheng, Mingxiang; Gong, Fei; Li, Yuan; Li, Xihong (Frontiers in Medicine, 2024)
Ultrasound has become a routine method for endometrial receptivity (ER) evaluation.However, there is controversy over the independent evaluation values of various ultrasound indicators. Some researchers have designed multi-indicator prediction systems, but their prediction values are uneven. To further our understanding of ER, we conducted this prospective cohort study to estimate ER noninvasively and effectively.Women who underwent the first frozen-thawed embryo transfer (FET) cycle from April 2019 to July 2021 were included in the study. On the day of transfer, transvaginal three-dimensional ultrasound examination was performed to evaluate ER, including endometrial thickness, morphology, volume, movement, blood flow and flow index. The clinical pregnancy rate was the primary outcome. Based on whether clinical pregnancy was achieved, enrolled patients were divided into pregnant and nonpregnant groups.This study analyzed 197 FET patients (139 pregnancies in total, 70.5%). The protective factors for clinical pregnancy included primary infertility (adjusted odds ratio (aOR), 1.98; 95% confidence interval (CI), 1.01-3.882; P=0.047) and more frequent endometrial peristalsis (aOR, 1.33; 95% CI, 1.028-1.722; P=0.03). Scores of 1 to 2 were assigned according to the relationship between different ultrasound indicators and the clinical pregnancy rate (CPR). The ER score of the patient was the sum of the scores of the 6 items. The ER score of the pregnant group was significantly higher than that of the nonpregnant group (7.40±1.73 vs. 6.33±1.99, P = 0.001). The CPR increased with an increasing ER score. The CPR in the ER < 6 group was significantly lower than that in the ER >6 group (45.5% vs. 75.6%, P = 0.001).A noninvasive ultrasound scoring system for ER was proposed. This system may provide a non-invasive guidance perspective, in conjunction with invasive assessments currently used in clinical practice, to achieve more effective embryo transfer.